2014
DOI: 10.1111/cei.12205
|View full text |Cite
|
Sign up to set email alerts
|

How immunosuppressive therapy affects T cells from kidney transplanted patients of different age: the role of latent cytomegalovirus infection

Abstract: SummaryThe average age of patients receiving renal transplantation is increasing as programmes have been established which support the donation of organs from elderly donors to older recipients. Little is known about the effect of immunosuppressive therapy on the immune system of older patients. In this study, T cell function and the composition of the T cell repertoire were analysed in immunosuppressed renal transplant recipients of different age and cytomegalovirus (CMV) status in comparison to age-and CMV-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Pearl et al (2005) revealed that residual T cells after depletion therapy share a single phenotype corresponding with effector memory T cells (CD3+CD4+CD45RA-CD62L-CCR7-), the study suggested that effector memory T cells are selectively resistant to the therapeutic depletion therapy. In contrast to this, other parts of adaptive immune system (CD4+, CD8+, IgG) are thoroughly influenced by post-transplant immunosuppression (Carter et al 2006, Gurkan et al 2010, Zand et al 2005 and therefore it is possible that homeostatic proliferation of T cells were not detected in our 2 time-points study.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Pearl et al (2005) revealed that residual T cells after depletion therapy share a single phenotype corresponding with effector memory T cells (CD3+CD4+CD45RA-CD62L-CCR7-), the study suggested that effector memory T cells are selectively resistant to the therapeutic depletion therapy. In contrast to this, other parts of adaptive immune system (CD4+, CD8+, IgG) are thoroughly influenced by post-transplant immunosuppression (Carter et al 2006, Gurkan et al 2010, Zand et al 2005 and therefore it is possible that homeostatic proliferation of T cells were not detected in our 2 time-points study.…”
Section: Discussionmentioning
confidence: 64%
“…The superior outcome of kidney transplantation is usually reached in LD (living donor) recipients, mainly due to shorter dialysis time and younger recipient age. Recently, T cell repertoire has also been described to be age-dependent in patients under immunosuppressive therapy (Welzl et al 2014). Similarly, the long term dialysis is associated with the premature aging of immune system (Betjes 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It may also bring to mind that the reduction in these cells in HCMV + patients could be due to immunosuppression therapy that transplanted patients received. It is evident that immunosuppression affects the frequency and composition of CD4 + T cell subsets, including a reduction in the IFN-γ producing Th1 and circulating follicular regulatory T cells (cTfr) [ 40 , 41 ]. To the best of our knowledge, the effect of immunosuppressive drugs on Th22 cells and cytokine has not been studied well.…”
Section: Discussionmentioning
confidence: 99%
“…However, the elevated CMV seroprevalence found in our study does not support this hypothesis. On the contrary, new findings have shown that latent CMV infection accelerates age-related changes in the T cell subsets in elderly patients, leading to a reduced proportion of naïve and early memory T cells and an increased number of CD8+ effector T cells which produce gamma interferon but do not have enough growth potential, making CMV disease more probable ( 15 , 16 ). Considering the previous finding, CMV prophylaxis in kidney transplant recipients older than 55 years might be beneficial.…”
Section: Discussionmentioning
confidence: 99%